THE STEREOTYPES OF THE MAIN CHARACTER IN AMANDA BROWN’S LEGALLY BLONDE NOVEL - Rina - Lestari (Pujangga: Jurnal Bahasa dan Sastra, 2021)
AbstractBecause of the improvement in every part of human life, the novel has become a famous literary work that can reflect the condition of society. The research entitled "The stereotypes That Elle Woods, The Main Character, Got in Amanda Brown's Legally Blonde Novel". The background of the study is based on the writer's interest in the story, the interesting, special and unique characters and conflicts in the story. This novel, apart from being based on the real experience of the author, describes a woman named Elle got stereotypes in Stanford Law School. This research was conducted by using a descriptive method and a qualitative approach. In preparing and completing the research, the writer collect the data through reading novel repeatedly, library and internet research. The writer looks for the theories that is accordance with the observation process from the opinions of experts, journals and books. The aims of the research is to answer the problems of the research which focuses on the stereotypes that Elle, the main character, got in Legally Blonde Novel. the author chooses feminism approach which has the strongest realtionship with the topic and uses a Psychological approach to analyze the characters and the stereotypes more deeply that appear in the novel. The theory is used in this research is the theory of Streotype that is used to find the women stereotype in the novel. The result of this research shows that there are some stereotype categories that have been used in this novel, Gender, Physical feature, Occupation and Socioeconomic status. More over the research indicates that Elle is presented as a female character who breaks the women stereotype under prejudice and discrimination especially in Stanford Law School.  keywords: character, stereotype, prejudice and discrimination